Basic School Dropout in Ghana: A Case Study of the Amansie West District (Journal of Science and Technology, 2016)
In view of the increasing cost of education the persistent phenomenon of school dropout has become a constant worry to all stakeholders. The focus of this paper was to assess the trend of basic school dropout in Amansie West, a predominantly rural district in Ghana and to further determine the main causes and policy implications of the phenomenon in the district. Analysis of the data revealed a downward trend in the dropout rates. At the primary school level, the dropout rate reduced from 5.4 percent in 1998/99 to 4.5 percent in the year 2000/01. At the Junior Secondary School (JSS) level, the dropout rate also reduced from 9.7 percent in 1998/99 to 6.7 percent in 2000/01. This trend was attributed to the diversification of the income sources of parents, which enabled them to earn more income to take care of their wards in school. Further analysis of data gathered revealed that about 45.4% of the parents of school dropouts in the district were extremely poor with annual incomes less than ¢600,000. The views of all stakeholders of education in the district confirmed that the causes of basic school dropout were mainly poverty related. In view of the strong inverse relationship between rates of school dropout and income levels it is recommended that pro-poor programmes be initiated and implemented in order to increase enrolment and retention of children in school for the ultimate benefits of public investment in education to be derived.